Jet Oil Production Process Using Non CNC Tools at PT Teknik Jaya Component - Deyan Satrio; Viktor Naubnome (CV. Rayyan Dwi Bharata, 2024)
Technological developments which are currently increasingly being felt are driving an increase in the number of people, the increase in population, especially in Indonesia, has also led to an increase in the need for manufacturing. Manufacturing in Indonesia is currently developing rapidly along with the development of science and technology. In Indonesia, manufacturing is not just an object or part of something but also has an important role in daily activities regarding certain tools. In this research, the method of direct observation was used during the testing process. The research results show that the use of non-CNC machines in the jet oil production process at PT. Teknik Jaya Component has high efficiency. This machine is capable of making jet oil quickly and producing quality products in large quantities. On non-CNC machines, the use of jigs/chucks is very influential in producing products in large quantities. The use of non-CNC machines also provides efficiency in material consumption when cutting, for example. Because in the non-CNC process the material has been cut into small parts, so less material is wasted during ingestion. The conclusions in this research include recommendations or further improvements in the non-CNC machine production process. This could involve technology updates, improved operational procedures or more efficient use of raw materials.